Intravenous Thrombolysis After Dabigatran Reversal by Idarucizumab: A Systematic Review of the Literature - Frol, Senta; Sagris, Dimitrios; Pretnar Oblak, Janja; Šabovič, Mišo; Ntaios, George (Frontiers in Neurology, 2021)
Idarucizumab achieves instant reversal of anticoagulation and enables intravenous thrombolysis (IVT) in dabigatran-treated acute ischemic stroke (AIS) patients. AIS in dabigatran-treated patients is a rare event, therefore the experience is limited. A review of all published cases was performed to evaluate the safety and effectiveness of this therapeutic strategy. We searched PubMed and Scopus for all published cases of IVT after reversal with idarucizumab in dabigatran-treated AIS patients. The outcomes were safety assessed by hemorhagic transformation (HT), symptomatic intracranial hemorrhage (SICH) and death, and efficacy assessed by National Institutes of Health Stroke Scale (NIHSS) reduction. We identified 251 AIS patients (39,9% females) with an average age of 74 years. HT, SICH and death were reported in 19 (7.6%), 9 (3.6%) and 21 (8.4%) patients, respectively. Patients experiencing HT presented with more severe strokes (median NIHSS on admission: 21 vs. 8, p<0.001; OR:1.12, 95%CI:1.05-1.20). After IVT there was a significant NIHSS reduction of 6 points (IQR:3–10, p<0.001) post-stroke and linear regression revealed a correlation of admission NIHSS to NIHSS reduction (p<0.001). In this systematic review of all published cases of IVT in dabigatran-treated AIS patients after reversal with idarucizumab the rates of HT, SICH and mortality, as well as NIHSS reduction, were comparable with previous studies in non-anticoagulated patients. This provides reassuring evidence about the safety and efficacy of this therapeutic strategy.